Analyzing Community Saving Behavior at the 'Usaha Bersama' Savings and Loan Cooperative - Hardiansah, Abu; Musthofa , M. Arif; Khoiratun Nisak, Sayida; Daud; Kartika Devi, Erwina (CV. Civiliza Publishing, 2025)
This study investigates the saving behavior of members of the “Usaha Bersama” Savings and Loan Cooperative in Merbau Village, Mendahara District, utilizing the Theory of Planned Behavior as the analytical framework. Employing a qualitative approach through interviews, observations, and documentation, the research uncovers the complex interplay of economic, social, and cultural factors influencing members’ saving habits. Findings reveal that ease of access, social proximity, trust in cooperative management, and local cultural values—particularly the principle of ta’awun (mutual cooperation)—significantly shape saving behavior. Although savings amounts tend to be small and irregular due to fluctuating agricultural incomes, saving remains an integral part of the community’s strategy to manage economic uncertainty and urgent needs. The study highlights the cooperative’s innovative flexible deposit policy and transparent, participatory management as key drivers of member engagement and loyalty. Implications emphasize the importance of inclusive cooperative models, continuous financial education, and culturally grounded policies in promoting sustainable savings practices and enhancing rural economic empowerment. This research contributes practical insights for cooperative development and policy formulation aimed at strengthening community-based financial inclusion in underserved rural areas